2001
DOI: 10.1086/323214
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Ωmwith theROSATDeep Cluster Survey

Abstract: We analyze the ROSAT Deep Cluster Survey (RDCS) to derive cosmological constraints from the evolution of the cluster X-ray luminosity distribution. The sample contains 103 galaxy clusters out to z^0.85 and Ñux limit ergs s~1 cm~2 (RDCS-3) in the [0.5È2.0] keV energy band, F lim \ 3 ] 10~14 with a high-redshift extension containing four clusters at 0.90 ¹ z ¹ 1.26 and brighter than F lim \ 1 ] 10~14 ergs s~1 cm~2 (RDCS-1). We assume cosmological models to be speciÐed by the matter density parameter the rms Ñuct… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
269
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 276 publications
(297 citation statements)
references
References 60 publications
25
269
3
Order By: Relevance
“…Several X-ray cluster samples have been constructed from previous X-ray missions and have been used for a variety of astrophysical studies (e.g. Romer et al 1994;Forman et al 1978;Scharf et al 1997;Vikhlinin et al 1998;Böhringer et al 2000Böhringer et al , 2004Borgani et al 2001;Burenin et al 2007). The current generation of X-ray satellites, XMM-Newton, Chandra, and Suzaku, provided follow-up observations of individual clusters that allowed a precise determination of their spatially resolved spectra (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Several X-ray cluster samples have been constructed from previous X-ray missions and have been used for a variety of astrophysical studies (e.g. Romer et al 1994;Forman et al 1978;Scharf et al 1997;Vikhlinin et al 1998;Böhringer et al 2000Böhringer et al , 2004Borgani et al 2001;Burenin et al 2007). The current generation of X-ray satellites, XMM-Newton, Chandra, and Suzaku, provided follow-up observations of individual clusters that allowed a precise determination of their spatially resolved spectra (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Being the most massive bound systems in the universe, they trace the latest stage of structure formation. Their abundance and mass as a function of redshift are thus highly indicative of how the growth of the cosmic density fluctuations occurs and can thus be used to constrain the matter content, the initial power spectrum normalisation and the expansion history of the universe (Eke et al 1998;Borgani et al 2001;Reiprich & Böhringer 2002;Allen et al 2003;Schuecker et al 2003;Henry 2004;Vikhlinin et al 2009;Mantz et al 2010;Rozo et al 2010;Sehgal & et al 2011;Planck Collaboration et al 2014a;Benson et al 2013;Mantz et al 2014). …”
Section: Introductionmentioning
confidence: 99%
“…The lesson from the previous calculation is that taking account of non-sphericity in collapse and the fact that massive clusters accrete matter quasi-continuously gives rise to a noteworthy change in the prediction of cosmological parameters, as Ω m . In order to check the previous trend, we have also estimated the value of Ω m following Borgani et al (2001). Analyzing the ROSAT Deep Cluster Survey (RDCS) and using the XLF to obtain constraints on cosmological parameters, Borgani et al (2001) found that Ω m = 0.35 +0.13 −0.10 .…”
mentioning
confidence: 99%